Positive Long-Run Capital Taxation: Chamley-Judd Revisited - Straub, Ludwig and Werning, Ivan (American Economic Review)
According to the Chamley-Judd result, capital should not be taxed in the long run. In this paper, we overturn this conclusion, showing that it does not follow from the very models used to derive it. For the main model in Judd (1985), we prove that the long-run tax on capital is positive and significant, whenever the intertemporal elasticity of substitution is below one. For higher elasticities, the tax converges to zero but may do so at a slow rate, after centuries of high tax rates. The main model in Chamley (1986) imposes an upper bound on capital taxes. We provide conditions under which these constraints bind forever, implying positive long-run taxes. When this is not the case, the long-run tax may be zero. However, if preferences are recursive and discounting is locally nonconstant (e.g., not additively separable over time), a zero long-run capital tax limit must be accompanied by zero private wealth (zero tax base) or by zero labor taxes (first-best). Finally, we explain why the equivalence of a positive capital tax with ever-increasing consumption taxes does not provide a firm rationale against capital taxation.
Keywords: Business Taxes and Subsidies,Value-added tax (VAT)